2018
DOI: 10.1002/ejoc.201800311
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bi‐ and Polyfunctional Isoxazoles from Amino Acid Derived Halogenoximes and Active Methylene Nitriles

Abstract: The reaction of chloroximes that have a protected amino group and active methylene nitriles under basic conditions has been shown to give functionalized 5‐aminoisoxazoles in yields of 37–81 %. This method has a broad substrate scope, including nitriles that contain either an electron‐withdrawing (i.e., CO2Me, CN, or SO2Me) or a heteroaryl group at the α‐position. Moreover, a malononitrile dimer was employed in analogous transformations, which led to the formation of polyfunctional isoxazolo[5,4‐b]pyridines. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Our previous experience with [ 3 + 2] cycloadditions showed that regioselectivity of the reaction can be controlled by using alkenes bearing a leaving group (e.g., bromo or dialkylamino substituents) as the starting materials. 51 To date, only a few examples of similar reactions with trifluoromethyl-substituted substrates were described in the literature, being limited to simple alkyl-or benzonitrile oxides and α,β-unsaturated esters (Scheme 2). 33,34,52 ■ RESULTS AND DISCUSSION Synthesis of isoxazoles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Our previous experience with [ 3 + 2] cycloadditions showed that regioselectivity of the reaction can be controlled by using alkenes bearing a leaving group (e.g., bromo or dialkylamino substituents) as the starting materials. 51 To date, only a few examples of similar reactions with trifluoromethyl-substituted substrates were described in the literature, being limited to simple alkyl-or benzonitrile oxides and α,β-unsaturated esters (Scheme 2). 33,34,52 ■ RESULTS AND DISCUSSION Synthesis of isoxazoles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Having intermediate halogenoximes, we started studying their interaction with dimethyl(vinyl)phosphine oxide (13). For the reaction, we chose conditions that previously proved themselves as efficient and reliable ones for a wide range of substrates [30]. Precisely, the reactions were carried out using a 1-to-1 ratio of the starting materials in the presence of a 1.3-fold excess of a weakly basic sodium bicarbonate in the ethyl acetate medium at room temperature.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…One should note that our research group has a profound experience in construction of polysubstituted isoxazoles and 4,5-dihydro analogs [30,31]. We have devised new and optimized known methods towards the heterocyclic platforms, which rely on 1,3-dipolar addition of in situ generated nitrile oxides from halogenoximes to diverse unsaturated partners.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The starting chloroximes 5 – 9 [both ( R )‐ and ( S )‐isomers were used in the case of chiral compounds] and enamines 10 – 18 were prepared according to the known procedures. Existing literature protocols for the [3+2] cycloaddition of halogenoximes and “push‐pull“ enamines varied in the reaction conditions, including AcOH in dioxane–H 2 O, neat Et 3 N, NaHCO 3 in EtOAc,, , and no promoter in dioxane , . In this work, we have used the conditions described in our previous works for similar transformations of the chloroximes 5 – 9 , , .…”
Section: Resultsmentioning
confidence: 99%
“…Existing literature protocols for the [3+2] cycloaddition of halogenoximes and “push‐pull“ enamines varied in the reaction conditions, including AcOH in dioxane–H 2 O, neat Et 3 N, NaHCO 3 in EtOAc,, , and no promoter in dioxane , . In this work, we have used the conditions described in our previous works for similar transformations of the chloroximes 5 – 9 , , . Thus, treatment of 5 – 9 with NaHCO 3 in EtOAc at room temp., followed by addition of 10 – 18 and subsequent stirring at room temp.…”
Section: Resultsmentioning
confidence: 99%